Respostas
respondido por:
9
Resposta: 13
Explicação passo-a-passo:
Olá,
* dados:
A(3,4) >> (x1, y1)
B(8,16) >> (x2, y2)
d = √(x2 - x1)² + (y2 - y1)²
d = √(8 - 3)² + (16 - 4)²
d = √(5)² + (12)²
d = √25 + 144
d = √169
d = √13²
d = 13
bons estudos!
respondido por:
3
A(3,4) >> (x1, y1) B(8,16) >> (x2, y2) d = /(x2 - x1)² + (y2 - y1)² d = / (8 - 3)2 + (16 - 4)² d = /(5)2 + (12)² d = /25 + 144 d = /169 d = /132 d = 13
Perguntas similares
5 anos atrás
5 anos atrás
7 anos atrás
7 anos atrás
8 anos atrás
8 anos atrás